Selective Oxidation of Cyclohexane to KA Oil Over Ce-Alpo-18 Molecular Sieves - Esther Leena Preethi, M.; Umasankari, A.; H.Rekha, C.; Palanichamy, M.; Sivakumar, T.; Pandurangan, A. (International Journal of Engineering and Technology, 2018)
The novel catalysts Ce-AlPO-18 with Al/Ce = 25, 50, 75 &100 were synthesized using hydrothermal synthesis procedure. The newly synthesized catalysts were characterized using physico-chemical techniques such as, X-ray diffraction (XRD) which confirmed AEI structure, diffuse reflectance spectroscopy (DRS-UV) confirmed the presence of both Ce3+ and Ce4+ in the framework and Fourier transform infrared spectroscopy (FT-IR) confirmed the complete removal of template molecule. The synthesized catalysts were tested for the oxidation of cyclohexane using air as the oxidant in a solvent free system and the results were discussed.
Keywords: AlPO-18; cerium; cyclohexane; hydrothermal synthesis; KA oil.